A versatile platform for fast and sensitive hydrogen peroxide detecting based on ferric-mediated radical reaction. (2nd January 2018) - Hu, Peng; Niu, Jing; Wang, Jiaojiao; Zhang, Ning
ABSTRACT: In this paper, we present a fluorescent biosensor that allows sensitive detection of hydrogen peroxide (H2 O2 ) by means of Fe 3+ -mediated radical reaction. This assay relies on the high reactivity of the hydroxyl radical generated by Fenton reagent. And the proposed method exhibits rapid response, low detection limit, high sensitivity as well as good stability and repeatability, which may provide an alternative method for biomolecular detection at physiological pH with simplicity. The detection limits for H2 O2 is 0.88 μM. In addition, given the simplicity, cost-effectiveness and reliability of this method, the proposed strategy can also be applied to the quantification of H2 O2 in real clinical samples.